Studies on structural, optical nonlinearity and antibacterial activity of Piperazine (bis) p-toluenesulfonate single crystal for optical limiting and biological applications - K. Balakrishnan; S. Sakthy Priya; A. Lakshmanan; P. Surendran; Karthik Kannan; P. Geetha; G. Vinitha; P. Praveen Kumar; P. Rameshkumar (Фізика і хімія твердого тіла, 2023)
Piperazine (bis) p-toluenesulfonate (PPTSA), an organic single crystal was synthesized and grown at environmental temperature by slow evaporation process using methanol as the solvent. The grown PPTSA crystal is from the triclinic system and belongs to the space group P1-. Powder X-ray diffraction was performed to ensure lattice parameters. Analysis and confirmation of functional groups and bonds were carried out through FT-IR spectral study. The optical characteristics were investigated using the UV-Vis spectrum such as the optical absorption, cut-off wavelength were calculated. The photoluminescence investigation was conducted to assess the luminous characteristics of grown crystal. The calculated NLO parameters like β, n2, and χ(3) were found to be 0.0495×10-4 (cm/W), 8.705×10-10 (cm2/W), 5.316×10-7 (esu) and Optical Limiting threshold value was found to be 3.074×10-3 (Wcm-2). Antibacterial studies were carried out to investigate the biological significance against selected foodborne germs.